Identifikasi Pengelolaan Kawasan Permukiman Kumuh di Kelurahan Sanua - Dheanissa Trifatika; Yulia Asyiawati (UNISBA Press, 2022)
Abstract. Sanua Village is a village that is indicated as high slum based on the Kendari Mayor's Decree No. 767/2014 concerning Determination of the Location of Slum Housing and Slum Settlement in Kendari City, with an area of ​​21 Ha. The problem identified in this area is that the sanitation conditions of the residential environment are not managed properly, so that it has an impact on the quality of the river in Sanua Village. This results in a reduction in the aesthetics of the area which affects the aesthetics and image of Kendari City. Based on this condition, it is necessary to conduct an identification study of area management in order to create a beautiful, comfortable, and worthy area to become a dwelling. The purpose of this study is to identify the management of residential areas in Sanua Village, using descriptive analysis method. From the results of the study conducted, that the condition of the existing house buildings only 45.47% that meet the standard of decent housing. Fulfillment of clean water, 68% of people use water sources from mountain springs, river conditions are not adequate, because 45.53% of people dispose of liquid waste and solid waste directly into the river. This happens because in the management of this area, the community does not understand the importance of area management. From this study it can be concluded that (1) in general, the condition of community housing does not meet the standard of decent housing; (2) generally the community disposes of liquid waste and solid waste directly into the river, thus having an impact on the condition of the river; (3) the community is less concerned and does not understand in the management of the area's environment. Some things that can be recommended include; (1) rejuvenating residential areas; (2) conduct socialization on the management of settlement sanitation; (3) invite the community to take part in the management of settlement sanitation through increasing public knowledge of healthy residential areas. Abstrak. Kelurahan Sanua merupakan Kelurahan yang terindikasi kumuh tinggi berdasarkan SK Walikota Kendari No. 767/2014 tentang Penetapan Lokasi Perumahan Kumuh dan Permukiman Kumuh Kota Kendari, dengan luas 21 Ha. Permasalahan yang teridentifikasi pada kawasan ini adalah kondisi sanitasi lingkungan permukiman tidak terkelola dengan baik, sehingga memberikan dampak terhadap kualitas sungai di Kelurahan Sanua. Hal ini mengakibatkan berkurangnya estetika kawasan yang berpengaruh terhadap estetika dan image Kota Kendari. Berdasarkan kondisi ini, perlu dilakukan studi indentifikasi pengelolaan kawasan agar dapat mewujudkan kawasan yang indah, nyaman, dan layak menjadi suatu hunian. Tujuan dari studi ini adalah teridentifikasinya pengelolaan kawasan permukiman di Kelurahan Sanua, dengan menggunakan metode deskriptif analisis. Dari hasil kajian yang dilakukan, bahwa kondisi bangunan rumah yang ada hanya 45,47% yang memenuhi standar hunian layak. Pemenuhan akan air bersih, 68% masyarakat menggunakan sumber air dari mata air pegunungan, kondisi sungai sudah tidak memadai, karena 45,53% masyarakat membuang limbah cair dan limbah padat langsung ke sungai. Hal ini terjadi karena dalam pengelolaan kawasan ini, masyarakat belum memahami akan pentingnya pengelolaan kawasan. Dari kajian ini dapat disimpulkan bahwa (1) pada umumnya kondisi hunian masyarakat belum memenuhi standar hunian layak; (2) umumnya masyarakat membuang limbah cair dan limbah padat langsung ke sungai, sehingga memberikan dampak terhadap kondisi sungai; (3) masyarakat kurang peduli dan kurang memahami dalam pengelolaan lingkungan kawasan. Beberapa hal yang dapat direkomendasikan antara lain; (1) melakukan peremajaan kawasan permukiman; (2) melakukan sosialisasi tentang pengelolaan sanitasi permukiman; (3) mengajak masyarakat untuk ikut berperan dalam pengelolaan sanitasi permukiman melalui peningkatan pengetahuan masyarakat akan kawasan permukiman sehat.